Commonwealth Realms jako relikt przeszłości. Zmiana formy rządów na Barbadosie - Woźniak, Martyna (Wydawnictwo Adam Marszałek, 2022)
After 70 years of Queen Elizabeth II’s Commonwealth Realms reign, only 15 countries remain, counting the United Kingdom. Barbados gained complete autonomy, becoming a republic after 55 years of independence. The purpose of this paper is to provide an outline of the process that took place in Barbados, from the time the British decided to settle on the Island, until it became a republic. The main research method used by the author, is source analysis and the point of reference is the Barbados Constitution Amendment Act of 28.09.2021, whereby from 30.11.2021, Barbados becomes a republic and all duties previously exercised by the Governor-General are exercised by the President.
Commonwealth Realms as a Relic of the Past. Change of the Political System in Barbados
Keywords: Commonwealth Relams; Great Britain; republic; monarchy; colonialism; Barbados; political system